2021
DOI: 10.1098/rsos.210910
|View full text |Cite
|
Sign up to set email alerts
|

Metal incorporated aminothiazole-derived compounds: synthesis, density function theory analysis,in vitroantibacterial and antioxidant evaluation

Abstract: The present study advocates the combined experimental and computational study of metal-based aminothiazole-derived Schiff base ligands. The structure and electronic properties of ligands have been experimentally studied by spectroscopic methods (UV-Vis, FT-IR, 1 H-NMR and 13 C-NMR), mass spectrometry, elemental analysis and theoretically by density function theory (DFT). Computational calculations employing the B3LYP/6-31 + G(d,p) functional of DFT were executed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 62 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Molecular electrostatic potential (MEP) studies showed the electrophilic substitution locations of the proposed combination, allowing reaction regions to be anticipated [44]. The colors red, blue, and green represent the negative, positive, and neutral areas of the MEP sections, respectively (Fig.…”
Section: Mep Analysismentioning
confidence: 99%
“…Molecular electrostatic potential (MEP) studies showed the electrophilic substitution locations of the proposed combination, allowing reaction regions to be anticipated [44]. The colors red, blue, and green represent the negative, positive, and neutral areas of the MEP sections, respectively (Fig.…”
Section: Mep Analysismentioning
confidence: 99%
“…The pattern of electron density within atoms and bonds across atoms is calculated using natural (localized) orbitals [48]. NBO profiling is used to identify electron acceptors and donor in various sections of the molecules [49]. This method can be used to inject dye electrons into the semiconductor's bandgap, with the C group acting as an anchoring factor.…”
Section: Natural Bond Orbitalsmentioning
confidence: 99%
“…Common global descriptors of chemical reactivity of biologically active derivatives can be discussed using DFT methods. [24][25][26] The study presents the synthesis, characterization, DFT calculation for the assignment of experimental IR and UV-Vis spectra and acetylcholinesterase inhibition effects of mononuclear ternary transition metal complexes (1-5) derived from azo-imine ligand 2-[(hydroxyimino) methyl]-4-[-phenyldiazenyl]phenol, H 2 L and 2,2'-bipyridine (bipy) as co-ligand (Figure 1) on AChEs of adults and nymphs of Ricania simulans. Because cell extract provides the closest composition to the cell medium, R. simulans extracts were used in the inhibition studies.…”
Section: Introductionmentioning
confidence: 99%